Management of lymphoma survivor patients in Italy: an evaluation by Fondazione Italiana Linfomi. Issue 1 (February 2021) - Minoia, Carla; Bari, Alessia; Nassi, Luca; Banzi, Rita; Gerardi, Chiara; Lenti, Valentina; Calabrese, Marco; Spina, Michele; Guarini, Attilio
Several outpatient models for the follow-up of cancer survivors have been developed worldwide. A multidisciplinary approach is often necessary to guarantee the best monitoring of long-term toxicities. Guidelines also indicate a close education on healthy lifestyles. In this context, we have analyzed the Italian follow-up modalities of lymphoma survivors, with the aim to have a starting line to hypothesize and plan the best model for Italian hematology centers.